Millennial Leadership as a Determinant of Work Enthusiasm: A Study in Government Institutions: Empirical Evidence from Indonesian Public Sector Employees - Ismi Rohmiana (SMARTINDO, 2025)
Purpose - This study investigates the influence of millennial leadership on employee work enthusiasm in the context of government institutions. The research aims to understand how leadership styles typical of the millennial generation, characterized by openness, adaptability, and a focus on work-life balance, affect employees' motivation and engagement. Design/methodology/approach - The study involved a random sample of 50 employees, and data was collected using a questionnaire. The hypothesis was tested using SmartPLS to analyze both direct effects and mediating analysis. Originality - While previous studies have explored leadership and work enthusiasm in private sector settings, this research offers originality by focusing on government institutions, highlighting how millennial leadership influences work enthusiasm within a bureaucratic context that is often overlooked in leadership studies. Findings and Discussion - The study revealed that millennial leadership has a significant positive effect on work enthusiasm among employees in government institutions. Furthermore, organizational culture was found to mediate the relationship between millennial leadership and work enthusiasm, indicating that a supportive and adaptive culture enhances the impact of leadership on employee motivation. Conclusion - Millennial leadership has a positive impact on employee work enthusiasm, with organizational culture acting as a mediator. The practical implication is that leaders in government institutions should focus on fostering an adaptive and supportive organizational culture to enhance employee engagement and motivation, ultimately improving overall performance.